Василий III: исторический роман : в 2 книгах / В. Артамонов ; [художник Н. Фадеева] - Артамонов Вадим Иванович (Советский писатель, 1991)
Экземпляры: (20231201) / Инвентарный номер: 25405 / Цена: 5.00 / Сис.шифр: Р2 / Авт.знак: А 86 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6